Modern Approach to Quantum Mechanics - John S Townsend (New Delhi Viva Books, 2010)
Inspired by Richard Feynman and J J Sakurai, A Modern Approach to Quantum Mechanics lets professors expose their undergraduates to the excitement and insight of Feynman's approach to quantum mechanics while simultaneously giving them a textbook that is well-ordered,logical,and pedagogically sound.
Keywords: QUANTUM MECHANICS -- QUANTUM THEORY